Pengaruh treatment terhadap peningkatan produktivitas industri mikro/kecil sasaran (export oriented product) dalam rangka peningkatan daya saing industri [studi kasus : di pulau lombok-ntb] - I G.A.K Chatur Adhi Wirya Aryadi; I Made Wijana; I Wayan Joniarta (Dinamika Teknik Mesin, 2017)
With the obtained value-indigo productivity on each SMEs, we can define improvement targets SMEs. By using reference values as a basis for selecting the smallest productivity of SMEs, then we can determine what we will improve. SMEs Dimas Silver and Songket gallery is a target implementation of productivity applied, because it has a partial productivity and totral smallest. Alternative workable is the addition of design and the use of E-Comers for both SMEs. Of the application of alternative sales increased 15% for Dimas silver and 10% to Songket Gallery. The impact of the increase in sales over the increased productivity of both productivity Dimas silver material partial first year of 2.86 and 3.28 for the second year. Average total productivity Songket Gallery 0.76 for the first year and 0.9 for the second year